Electrolyte and Acid-Base Disorders in the Renal Transplant Recipient - Pochineni, Vaishnavi; Rondon-Berrios, Helbert (Frontiers in Medicine, 2018)
Kidney transplantation is the current treatment of choice for patients with end-stage renal disease. Innovations in transplantation and immunosuppression regimens have greatly improved the renal allograft survival. Based on recently published data from the Scientific Registry of Transplant recipients, prevalence of kidney transplants is steadily rising in the United States. Over 210,000 kidney transplant recipients were alive with a functioning graft in mid-2016, which is nearly twice as many as in 2005. While successful renal transplantation corrects most of the electrolyte and mineral abnormalities seen in advanced renal failure, the abnormalities seen in the post-transplant period are surprisingly different from those seen in chronic kidney disease. Multiple factors contribute to the high prevalence of these abnormalities that include level of allograft function, use of immunosuppressive medications and metabolic changes in the post-transplant period. Electrolyte disturbances are common in patients after renal transplantation, and several studies have tried to determine the clinical significance of these disturbances. In this manuscript we review the key aspects of the most commonly found post-transplant electrolyte abnormalities. We focus on their epidemiology, pathophysiology, clinical manifestations and available treatment approaches.